2008
DOI: 10.1038/bjp.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the metabolic actions of galegine that contribute to weight loss in mice

Abstract: Background and purpose: Galegine and guanidine, originally isolated from Galega officinalis, led to the development of the biguanides. The weight-reducing effects of galegine have not previously been studied and the present investigation was undertaken to determine its mechanism(s) of action. Experimental approach: Body weight and food intake were examined in mice. Glucose uptake and acetyl-CoA carboxylase activity were studied in 3T3-L1 adipocytes and L6 myotubes and AMP activated protein kinase (AMPK) activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…Prolonged stimulation with metformin reduced the fold stimulation of glucose transport by insulin, yet this was likely to have occurred because of a non-significant increase in basal glucose transport rather than a decrease in insulin-stimulated glucose transport. A previous study also reported a modest tendency toward increased basal glucose transport in 3T3-L1 adipocytes stimulated with 0.3 mmol/l metformin for 24 h [41]. The data in the current study represent, to the authors' knowledge, the first report of the effect of metformin on insulin-stimulated glucose transport in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 74%
“…Prolonged stimulation with metformin reduced the fold stimulation of glucose transport by insulin, yet this was likely to have occurred because of a non-significant increase in basal glucose transport rather than a decrease in insulin-stimulated glucose transport. A previous study also reported a modest tendency toward increased basal glucose transport in 3T3-L1 adipocytes stimulated with 0.3 mmol/l metformin for 24 h [41]. The data in the current study represent, to the authors' knowledge, the first report of the effect of metformin on insulin-stimulated glucose transport in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 74%
“…AMPK is also activated by numerous drugs and xenobiotics. Some of these are in clinical use for the treatment of type 2 diabetes (e.g., metformin [Zhou et al 2001] and thiazolidinediones ), some are ''nutraceuticals'' (e.g., resveratrol from red wine [Baur et al 2006] and epigallocatechin gallate from green tea [Hwang et al 2007]), and some are plant products used in traditional herbal medicines in Europe (e.g., galegine, from which metformin was originally derived) (Mooney et al 2008) or Asia (e.g., berberine [Lee et al 2006] and hispidulin [Lin et al 2010]). One puzzling feature was how so many xenobiotics of very varied structure could all activate AMPK; it seemed unlikely that they would all bind directly to the kinase complex.…”
Section: Role Of Ampk Orthologs In Nonmammalian Eukaryotesmentioning
confidence: 99%
“…Many natural products derived from traditional medicine that were claimed to have beneficial effects in diabetes and cancer can also activate AMPK. They include resveratrol, epigallocathechin gallate, berberine, and quercitine (Mooney et al 2008, Turner et al 2008. Recent years have shown the development of novel pharmacological agents that can modulate AMPK directly with the hope that these compounds will be promising in the treatment of metabolic disorders.…”
Section: Main Drugs That Are Ampk Activatorsmentioning
confidence: 99%